Impact of stress on adolescents during puberty (part 2) - L.A. Strashok; L.I. Rak; H.M. Danylenko; A.V. Yeshchenko; V.L. Kashina-Yarmak; E.M. Zavelya; M.Yu. Isakova (Zdorovʹe Rebenka, 2023)
The second part of the presented article provides information on the activity of the pituitary, adrenal and sex glands in puberty and during stressful conditions. The relationship between hormones and neurotransmitters that ensure the activity of the body is described in detail, in particular, the effects of follicle-stimulating, luteinizing hormones, prolactin, somatotropic and adrenocorticotropic hormones, melatonin, cortisol, adrenaline and norepinephrine, estrogens, testosterone, etc. are given. The data of our own studies on the influence of physical activity of varying intensity (as a stress-modulating factor) on adolescents with different course of the puberty are presented. They confirmed a close relationship between the course of puberty and stress-dependent neuroendocrine factors, showed gender differences in the mechanisms of regulation during puberty. Particular attention in the article is focused on the main pathological conditions and diseases that can be provoked by severe or prolonged stress in adolescence. Features of the course of stress reactions in adolescents are associated with the still incomplete remodeling of regulatory structures. Along with increased vulnerability to stress factors, there is a high adaptive plasticity and vitality. Understanding the mechanisms of interaction between the neuroendocrine effects of stress and the restructuring of the body caused by puberty can contribute to the development of effective medical care measures to preserve the somatic and mental health of adolescents and maintain optimal resilience in adolescence.